2019
DOI: 10.1111/imj.14066
|View full text |Cite
|
Sign up to set email alerts
|

Hospital discharge data under‐reports delirium occurrence: results from a point prevalence survey of delirium in a major Australian health service

Abstract: ICD coding is inadequate to determine in hospital delirium incidence. Instead, a point prevalence detection of delirium using the methods described above could be used. Health services could apply the described survey method to evaluate their local initiatives for the improvement of delirium detection and prevention. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…Among the nine point prevalence studies included in the review, the majority were performed in a single country: Australia (Casey et al, ; Hosie et al, ), Denmark (Norbaek & Glipstrup, ), Ireland (Ryan et al, ), Italy (Bellelli et al, ), Scotland (Spiller & Keen, ) and UK (Giraud & Vuylsteke, ). One study (Elliott et al, ) included two countries: Australia and New Zealand; one study (Salluh et al, ) included 11 countries: Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Peru, Spain, USA and Uruguay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the nine point prevalence studies included in the review, the majority were performed in a single country: Australia (Casey et al, ; Hosie et al, ), Denmark (Norbaek & Glipstrup, ), Ireland (Ryan et al, ), Italy (Bellelli et al, ), Scotland (Spiller & Keen, ) and UK (Giraud & Vuylsteke, ). One study (Elliott et al, ) included two countries: Australia and New Zealand; one study (Salluh et al, ) included 11 countries: Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Peru, Spain, USA and Uruguay.…”
Section: Resultsmentioning
confidence: 99%
“…One study (Elliott et al, ) included two countries: Australia and New Zealand; one study (Salluh et al, ) included 11 countries: Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Peru, Spain, USA and Uruguay. All studies focused on inpatient settings: ICU ( n = 3; Elliott et al, ; Giraud & Vuylsteke, ; Salluh et al, ); acute care hospital ( n = 4; Bellelli et al, ; Casey et al, ; Norbaek & Glipstrup, ; Ryan et al, ); and palliative care unit or hospice ( n = 2; Hosie et al, ; Spiller & Keen, ). The sample size for the selected studies ranged from 47–1,867 participants, who were primarily older adults with a reported mean age range of 61–82 years and 42%–63% male.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocol was completed for 559, of whom 245 (43.9%) returned abnormal screening tests (4AT score of ≥1). Delirium was detected in 91 patients (16.3%) . We noted that delirium was found in some patients who had 4AT scores of 1‐3 and also that delirium was not found in some patients who had 4AT scores of 4 or more (refer to Table ).…”
Section: Resultsmentioning
confidence: 69%